Dobro wspólne jako nie-kapitalistyczna forma bogactwa. Antonia Negriego teza o kryzysie prawa wartości i jej konsekwencje - Szadkowski, Krystian (My University, 2014)
The core aspect of Antonio Negri’s political philosophy and the reading of “Marx beyond Marx”, that is the thesis on the crisis of law of value, was analyzed here in details. Thesis that Negri’s altermodern humanism, at least since the end of the 1960’s, is developing in the strict interrelationship with the thesis on the crisis of law of value was proposed. Together with an ontological assumption that we are living in the era of real subsumption of society under capital it creates the conceptual matrix of the project of the common. The main parts of this text explored the following problems: a) the context of the formulation of the thesis on the crisis of law of value; b) the meaning of the law of value in the Marx’s theory; c) Marxist debate on the status of law of value in socialism with reference to its usefulness for the projects of the alternative to capitalism; d) core aspects of the thesis; e) its consequences for the new theories of exploitation, antagonism and value for the present state of the development of capitalism. The aim of the text is to show the political meaning of the thesis of on the crisis of the law of value.
Keywords: Marks; Negri; dobro wspólne; teoria wartości; prawo wartości; operaizm; postoperaizm